Analisis Visual Penerapan Brand Equity Pada Video City Branding "Shining Batu" - Yogi Widya Saka Warsaa; Nicholaus Wayong Kabelen (Jurnal Desain Komunikasi Visual Asia, 2023)
The Object of this research is the video "Shining Batu" this video was published by the Government have aims to support branding activities and promotion to introduce the target audience, also create the image that the City of Batu is represented by the City Branding "Shining Batu" is a tourist destination that has various places for vacations, culinary, nature destination, and other park building. This study aims to measure and determine brand equity in branding activities presented in the video "Shining Batu". This research used a qualitative method that discussed in terms of audio and visual quality in terms of the presentation of each footage visualized and correlated with the city branding of the Batu City Government, namely "Shining Batu". The results of this study are in the form of several analyses related to visual communication design disciplines, especially branding, and videography.